Violence Prevention Through Bodybuilding - Goudkov, Dmitri (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The current study focuses on young men around the world in their teens and twenties who are considered at risk -- that is, those young men who have no access to education and economic opportunities and who have no stabilizing social anchors, such as family, teachers, coaches, church, and friends. These men are at risk of feeling less masculine. Their emasculation then leads to low self-esteem, and it is the fundamental assumption of this study that such young men with low self-esteem see violence as their last resort to regain their self-esteem and self-respect at the expense of their own or other peoples lives. Bodybuilding offers an alternative route to higher self-esteem. A number of factors set bodybuilding apart from other sports that offer the same approach to violence prevention. First, building muscular bodies already attracts millions of young men around the world. Second, bodybuilding is a rare sport, in which progress, a more muscular body, is visible to all. Progress in most other sports is visible only as young men play them. Third, bodybuilding is not competitive, which avoids the danger of many contact sports that thrive on competition. Last, but not least, bodybuilding is self-perpetuating and self-reliant, long after an official bodybuilding program is over. As with anything powerful, bodybuilding can be counterproductive if left to its own devices, but this study offers ways to avoid potential pitfalls; it has addressed the issue of testosterone, abuse of steroids, and disconnect between bodybuilding and reality. Just as martial arts reduce aggressive tendencies when they focus on self-actualization rather than simply self-defense, bodybuilding can ultimately prevent violence when, instead of getting trapped in the narcissism of bodybuilding, young men learn that controlling their destinies is similar to controlling their muscles.